2010
DOI: 10.1021/bi901753h
|View full text |Cite
|
Sign up to set email alerts
|

The Clustering and Spatial Arrangement of β-Sheet Sequence, but Not Order, Govern α-Synuclein Fibrillogenesis

Abstract: The intrinsically unstructured protein α-synuclein (aS) is prone to misfold into cytotoxic β-sheet-rich oligomers and amyloid fibrils that underlie the pathogenesis of Lewy body diseases such as Parkinson's disease. An important, recognized fibrillogenesis parameter is amino acid content, whereas the influence of amino acid sequence distribution is not as well understood. The fibril core of aS encompasses five regions of high β-sheet propensity, termed β1-β5. Using four aS variants with identical amino acid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 57 publications
2
28
0
1
Order By: Relevance
“…28 Finally, the oligomerization of larger peptides and full-length proteins might obey similar principles but usually needs to be accompanied by a substantial change or loss of intra-peptide interactions. Moreover, aggregation is facilitated by transient misfolding or unfolding events of particular aggregation-prone segments, which populate amyloid competent conformers, such as hairpin motifs or intra-molecular β-strand stacks in natively disordered peptides 41,45,54,90 or accessible self-complementary stretches on protein surfaces. 22,23,67 Recent findings furthermore suggest that while oligomer formation might be facilitated by small segments and their local properties, the eventual maturation toward fibrillar structure will involve a remodeling stage to further incorporate and accommodate residues into the β-strands.…”
Section: Discussionmentioning
confidence: 99%
“…28 Finally, the oligomerization of larger peptides and full-length proteins might obey similar principles but usually needs to be accompanied by a substantial change or loss of intra-peptide interactions. Moreover, aggregation is facilitated by transient misfolding or unfolding events of particular aggregation-prone segments, which populate amyloid competent conformers, such as hairpin motifs or intra-molecular β-strand stacks in natively disordered peptides 41,45,54,90 or accessible self-complementary stretches on protein surfaces. 22,23,67 Recent findings furthermore suggest that while oligomer formation might be facilitated by small segments and their local properties, the eventual maturation toward fibrillar structure will involve a remodeling stage to further incorporate and accommodate residues into the β-strands.…”
Section: Discussionmentioning
confidence: 99%
“…Following ion exchange chromatography using HiTrap Q-Sepharose (GE Healthcare), any residual DNA was digested with 500 Kunitz units of DNase I (bovine pancreas; EMD Chemicals, Inc.) for 1 h at 37°C to exclude spectral contamination in concentration measurements. The desired intramolecularly disulfide-bonded proteins, ␣S(Cys 11 -Cys 81 ) and ␣S(Cys 11 -Cys 83 ), were then separated from covalently linked protein oligomers by gel filtration employing a Sephacryl S-100 HR 26/60 column (GE Healthcare) as described previously in detail (34). Sample purity was verified by SDS-PAGE (supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…interconversions of vesicle-bound ␣S segments may bear relevance to accessing its misfolding pathway (32,33), which initially exhibits characteristics of a conformational search (34). At a given time, protein structures are generally characterized by a single well defined conformation, and the existence of multiple parallel ␣S conformations would be an interesting deviation from this paradigm.…”
mentioning
confidence: 99%
“…[3][4][5] Numerous biophysical and biochemical experimental studies have made substantial advances and revealed some common features such as cross-β X-ray diffraction patterns. 6,7 Regardless of these advances, detailed information on the structures and formation mechanism of protein aggregates at atomistic levels, and also the interpretation of experimentally revealed structural features based on atomic level studies, are rather limited. For example, we do not yet have clear explanations for the following questions: what molecular features give rise to cross-β spine structure?…”
Section: Introductionmentioning
confidence: 99%